You have got items to show off your pride: the effects of pride on preference for attention-grabbing products - Ahn, Hee-Kyung; Kim, Seung-Hwa; Ke, Wen Ying (European journal of marketing, 2021)
Purpose This study examines the impact of incidental pride on consumer preference for attention-grabbing products. This effect is mediated by the desire to gain attention. This study also shows that the effect of incidental pride is qualified by visibility of consumption. Design/methodology/approach Using two studies with between-subjects designs, this research examines the difference in preferences for attention-grabbing products between hubristic and authentic pride. Findings Individuals who experience hubristic pride (vs authentic pride) show greater preference for attention-grabbing products and have a strong desire to gain attention from others. However, when consumption is perceived as private (vs public), preferences for attention-grabbing products weaken for those who experience hubristic pride. Research limitations/implications This research studies the effect of incidental pride on consumer preference. By examining dispositional pride effects, future research may expand these findings, which enrich the literature on emotion. Future research can identify the potential mechanism for the relationship between authentic pride and preference for attention-grabbing products in the context of private consumption. Practical implications Marketers and salespersons can guide and recommend products with attention-grabbing features to customers celebrating a friend’s success in recognition of their innate ability. Second, marketers may encourage consumers to buy attention-grabbing products with targeted advertising or emotion-eliciting advertising (i.e., evoke a certain type of pride). Originality/value While prior studies focused on basic emotions, this research has investigated self-conscious emotions that are central to consumer behavior. This research contributes to the understanding of self-conscious emotions that affect consumers’ behavioral responses in unrelated situations. Investigating the two facets of pride, the findings show the impact of pride on the preference for attention-grabbing products and reveals that visibility of consumption moderates the effect of pride.